2013
DOI: 10.3892/ijo.2013.2167
|View full text |Cite
|
Sign up to set email alerts
|

Close correlation between MEK/ERK and Aurora-B signaling pathways in sustaining tumorigenic potential and radioresistance of gynecological cancer cell lines

Abstract: Both Aurora-A and -B kinases have been implicated in tumorigenesis; and as such, they represent an attractive therapeutic target. Recent studies found that Aurora-A is a downstream target of mitogen-activated protein kinase 1/ERK2, while Aurora-B has been found to be a prognostic/predictive therapeutic target for epithelial cancer. In a wide range of human cancers, the Ras/Raf/MEK/ERK/MAP kinase pathway is enhanced and the cellular response to growth signals is known to increase. The purpose of this study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 44 publications
2
27
0
Order By: Relevance
“…In this study, the results indicated that down-regulating ERK1/2 with U0126 inhibited Hela and C33A cells proliferation, induced cell apoptosis, arrested the cell cycle in G0/G1 stage, and decreased the proportions of G2/M stages. It was consistent with the previous finding that U0126 decreased the tumorigenic potential of cervical cancer and improved the radiation response in all cellular models [25]. However, an opposite result was observed by a recent study.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, the results indicated that down-regulating ERK1/2 with U0126 inhibited Hela and C33A cells proliferation, induced cell apoptosis, arrested the cell cycle in G0/G1 stage, and decreased the proportions of G2/M stages. It was consistent with the previous finding that U0126 decreased the tumorigenic potential of cervical cancer and improved the radiation response in all cellular models [25]. However, an opposite result was observed by a recent study.…”
Section: Discussionsupporting
confidence: 85%
“…Mutational activation of the Ras–Raf–MEK–ERK kinase pathway is frequently observed in a wide range of human cancers, including gynecological cancer, and PHB has been demonstrated to be mandatory for this signaling pathway 15,16. As listed in Table 2, PHB was involved in tumor progression in ovarian cancer 17,18.…”
Section: Resultsmentioning
confidence: 99%
“…(Fredholm, IJzerman, et al, 2001;Schulte & Fredholm, 2003). With respect to gynecological cancer, using U0126, an inhibitor of MEK/ERK or AZD1152, an inhibitor of Aurora-B kinase, oncogenic serine/threonine kinase positively affected by Ras/Raf/MEK/ERKs pathway, declined tumorigenic potential and radioresistance phenotype through enhancing apoptotic mechanisms in diverse gynecological cancer cell lines including Ishikawa, HeLa, CASKI, and SiHa cells (Marampon et al, 2014), suggesting that inhibition of Ras/Raf/MEK/ERKs pathway could be a novel therapeutic procedures for gynecological cancer. Furthermore, it has been shown that nucleoside transporters could also regulate adenosine concentrations in gynecological cancers.…”
Section: Discussionmentioning
confidence: 99%